The North American Immune Tolerance Registry: Practices, Outcomes, Outcome Predictors - DiMichele, D. M.; Kroner, B.L.; The North American Immune Tolerance Study Group (Thrombosis and Haemostasis, 2002)
The North American Immune Tolerance Registry was initiated to study of immune tolerance (ITT) in Canada and the United States with respect to: 1) therapeutic regimens in use for haemophilia A (HA) and B (HB) inhibitor patients; 2) therapeutic outcomes; 3) potential predictors of successful outcome and 4) complications of therapy. Data on 188 ITT courses was collected by questionnaire from 60 haemophilia centers from 1993-99. Among the completed courses, the overall ITT success rate was 70% (115/164) for all HA and 31% (5/16) for all HB. Outcome parameters noted to be predictive of ITT success for all HA were 1) pre-ITT induction (p = 0.003), 2) ITT peak (p = 0.007) and 3) historical pre ITT peak (p = 0.04) inhibitor titres. An inverse correlation between total daily dose (units/kg/day) and success: (80% with under 50; 71% with 50-99; 73% with 100-199; and 41% with ≥ 200, p = 0.01) was found. Outcome predictors were not evaluable for HB, although adverse reactions to therapy, including nephrotic syndrome, and access complications were more common among failed courses. Infection most often complicated the use of access catheters. These results are discussed within the context of the international ITT registry and upcoming prospective ITT study.
Keywords: Hemophilia A; hemophilia B; inhibitor therapy; immune tolerance